Effect of Different Disinfectants on Grey Water Quality during Storage - Tal, Tom; Sathasivan, Arumugam; Bal Krishna, KC (University of Technology, Sydney (UTS) and Xi'an University of Architecture and Technology (XAUAT), 2011)
Grey water offers potential to save large amount of potable water resources. However, grey water can only be stored for up to 24 hours in most parts of the world because of the fast deterioration in quality due to bacterial growth. Several physical, biological and chemical treatment methods or combination of them can be employed to safely increase the retention time. In this study, grey water sample collected from a typical urban house in Western Australia was used to investigate the effectiveness of physical, chemical and combination of them to treat for stor-ing longer time. For chemical treatment, chlorine, chloramine and hydrogen peroxide were assessed whereas for physical treatment, grey water samples were filtered through 11μm filter paper to remove large suspended solids. Chloramine was found to be effective for storing longer time without combination of physical treatment. It was noted that organic matter present in grey water induces a greater chlorine demand and prevent proper disinfection. Chlorine was found to be highly reactive with impurities found in grey water, so removal of these impurities is es-sential through filtration. Hydrogen peroxide was ineffective at low doses and was the weakest of the three disinfec-tants.